Effects of Temperature and Strain Rate on the Dynamic Fracture Properties of HTPB Propellant. Issue 4 (13th March 2015) - Long, Bing; Chang, Xinlong; Hu, Kuan; Zhang, Youhong
Abstract: In order to study the influence of temperature and strain‐rate on HTPB propellant fracture capability under impact loading conditions, a dynamic fracture experiment at different temperatures was carried out by using the cracked straight‐through Brazilian disc (CSTBD) specimen on the split Hopkinson pressure bar (SHPB), and the dynamic initiation fracture toughness of the HTPB propellant was obtained. Experimental results indicate that the proposed dynamic fracture testing for the HTPB propellant is effective. The dynamic initiation fracture toughness is obviously sensitive to temperature and strain‐rate, and its value increases with decreasing temperature and increasing strain rate, and a linearity relationship exists between the fracture toughness and the logarithm of the strain rate, and the linearity also increases with increasing loading rate. A master curve of quadratic function for the fracture toughness was obtained.